2018
DOI: 10.1038/s41598-018-31577-1
|View full text |Cite|
|
Sign up to set email alerts
|

Eye movement characteristics reflected fatigue development in both young and elderly individuals

Abstract: Fatigue can develop during prolonged computer work, particularly in elderly individuals. This study investigated eye movement characteristics in relation to fatigue development. Twenty young and 18 elderly healthy adults were recruited to perform a prolonged functional computer task while their eye movements were recorded. The task lasted 40 minutes involving 240 cycles divided into 12 segments. Each cycle consisted of a sequence involving memorization of a pattern, a washout period, and replication of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 71 publications
(78 reference statements)
4
44
0
Order By: Relevance
“…Given the importance of eye movements for visual perception, there has been a surge of interest in eye movements with numerous studies being conducted to clarify what kind of information can be derived from eye movements. A number of studies have suggested that eye movement, blinking rate, and fixation duration can be linked to the task, information processing, stress level, fatigue and loads [ 57 , 58 , 59 ]. Many investigators have reported that an increase in eye movement when the task increases in difficulty [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given the importance of eye movements for visual perception, there has been a surge of interest in eye movements with numerous studies being conducted to clarify what kind of information can be derived from eye movements. A number of studies have suggested that eye movement, blinking rate, and fixation duration can be linked to the task, information processing, stress level, fatigue and loads [ 57 , 58 , 59 ]. Many investigators have reported that an increase in eye movement when the task increases in difficulty [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…In both experimental sessions, participants were asked to perform a cyclic computer task [38] for approx. 31–35 min (Fig 1).…”
Section: Methodsmentioning
confidence: 99%
“…To implement the biofeedback system, a statistical model of fatigue was developed based on previously collected oculometrics dataset (OLDSET) during an identical computer task [38]. The OLDSET consisted of the oculometrics extracted from gaze positions and pupil dilations, and KSS ratings from 38 participants in 40-min samples of an identical computer task without micro-breaks as described in [38]. The state of fatigue for each segment was assigned based on the KSS scores obtained after each segment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations